Duncan L. Du Bois, Sugar and Settlers: A History of the Natal South Coast 1850- 1910 (Historia, 2021)
This recent publication by Duncan L. Du Bois is an interesting and rich account of the history of Natal's South Coast during colonial times. It is based on Du Bois's PhD thesis entitled "Sugar and Settlers: The Colonisation of the Natal South Coast, 1850-1910", which was accepted by the University of Kwazulu-Natal in 2014. Natal's South Coast during colonial times was known for its cultivation of coffee, cotton and sugar. However, it was the cultivation and production of sugar which promoted the arrival of settlers and the extension of Natal's southern frontier to the Mtamvuna River.
Keywords: Book reviews; Sugar; Kwazulu-Natal; Mtamvuna